PENGARUH PERMAINAN KIRIMKAN ANGKA ITU TERHADAP KEMAMPUAN MENGENAL KONSEP LAMBANG BILANGAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 2 KOTA PEKANBARU - Dini Anggia; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is to to determine the effect of the game " send me the number was " the ability to recognize the concept emblem numbers 5-6 years old children in TK Negeri Pembina 2 Pekanbaru City. The population and sample of this research is children aged 5-6 years amounted to 19 children. Data collection techniques were used that observation. Data analysis techniques used in this research is the analysis of the Wilcoxon test. The result showed the effectiveness of the game by 51.95 % and a significant value was 0.000 for 0.000 < 0.05, then H0 rejected Ha accepted. This means that there are significant game " send me the number was " the ability to recognize the concept of the symbol of the number of children aged 5-6 years. To find out the hypothesis is accepted or rejected based on the data SPSS for windows vesion 16 it can be seen from the comparison tcount with t table ie from the calculation of the t test, it appears that the results count z = 3.845 and the result sign of 0.000 < 0.05, so Ha is received H0 rejected. Thus Ho = rejected and Ha = acceptable. From this study it can be concluded that the game "send me the number was" could be a medium of learning in developing children's ability to recognize the concept of numbers emblem. The game " send me the number was " the ability to recognize the concept emblem numbers in children aged 5-6 years in TK Negeri Pembina 2 Pekanbaru City effect of 51.95 %. It has been suggested that children's ability to recognize the concept of the symbol of the number of children affected by another factor of 48.05 % .Keywords: ability to know the concept symbol number, the game send me the number was